To the Question of Source Basis of the Problem of Pre-Professional Training of Foreign Students of the Ukraine’s Higher Medical Institutions (Culturological Aspect) - Artem Belous (Pedagogical Discourse, 2013)
In the article the analysis of the available source basis on the problem of pre professional training of foreign students in the Ukraine’s higher educational establishments is given. Quite a small number of works of Ukrainian scientists, who researched some questions of this problem is revealed. By the example of medical higher institutes it is determined that perspective directions of research might be those directions that rely on the positions of reform about health protection and modern transformations in education. Special attention is given to consideration of the cultural-historical aspect, which is defined as a basis for establishment of professional interaction between representatives of different areals of cultures. In this aspect the author relies on the classification of cultural areals in terminology of «the East» and «the West», which is generally accepted in humanities. The conclusions of the article may be considered as the tasks for the further researches in this sphere.